Far Away : Hat Making in UWEC's Costume Shop - Griffin, Katie (My University, 2014)
The purpose of this study was to document the creation of hats for the stage production of Far Way at the University of Wisconsin--Eau Claire Music and Theatre Arts Department costume shop.
Color poster with text and photographs.
Keywords: Costume design--Hats; Far Away (play); Music and Theatre Arts Department--University of Wisconsin--Eau Claire; Posters